Antifouling Field‐Effect Transistor Sensing Interface Based on Covalent Organic Frameworks. (26th March 2020) - Yang, Lei; Jin, Yuqing; Wang, Xuejun; Yu, Bin; Chen, Renzhong; Zhang, Cong; Zhao, Yan; Yu, Yuguo; Liu, Yunqi; Wei, Dacheng
Abstract: Due to the complexity of detection environments, field‐effect transistor (FET) sensors face the problem of fouling in practical applications. Existing antifouling strategies normally block the sensing sites and decrease the detection sensitivity. It remains a great challenge to achieve antifouling and sensitive detection. Here, a strategy is developed to use covalent organic frameworks (COFs) as the sensing interface. Owing to their unique crystalline mesoporous structure, the COFs not only encapsulate and prevent the channel from being fouled but also provide a large specific surface area modified with receptors. This approach enables the detection of 10 −10 m Hg 2+ within 50 ms in a ≈30 ppm poly‐(3, 4‐ethylenedioxythiophene):poly‐(styrenesulfonate) solution and weak neural potential signals in complex bio‐environment, which is among the best performance for antifouling FET sensors. The COF interface enables highly sensitive and antifouling detection together with a fast response and large response range, which shows its great potential in high‐performance antifouling FET sensors. Abstract : A covalent organic framework (COF)‐based sensing interface is developed for antifouling field‐effect transistor (FET) sensor. Owing to the unique crystalline mesoporous structure, the COFs protect the channel from foulants and provide large specific surface area modified with receptors. Thus, in a complex environment, 10 −10 m Hg 2+ or weak neural potential signals can be detected.